1966
DOI: 10.1017/s0028688500003246
|View full text |Cite
|
Sign up to set email alerts
|

Paulus und die Weisheit

Abstract: Es soil nicht nur dieallgemeine, religionsgeschichtliche Frage gestellt werden, wie weit Paulus faktisch in der Tradition der jüdischen Weisheit steht. Die Frage soil präzisiert werden: Wie geht Paulusaktivmit dieser Weisheit um, indem er ihre Methoden verwendet, ihre Gedanken verarbeitet, im Stil der Weisheitliterarischgestaltet? Vielleicht ergeben sich aus dieser Fragestellung Gesichtspunkte für ein Urteil in dem immer noch offenen Streit darüber, wie das sachliche Zentrum seiner Theologie zu bestimmen sei: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1968
1968
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…45 Hans Conzelmann vermutete die Herkunft des Paulus aus eine Weisheitsschule, die er in seinen Missionszentren weiter betrieb. 46 Indiz für weisheitstheologisches Denken ist für beide Ausleger insbesondere der Kolosserbrief.…”
Section: Weisheit Bei Paulusunclassified
“…45 Hans Conzelmann vermutete die Herkunft des Paulus aus eine Weisheitsschule, die er in seinen Missionszentren weiter betrieb. 46 Indiz für weisheitstheologisches Denken ist für beide Ausleger insbesondere der Kolosserbrief.…”
Section: Weisheit Bei Paulusunclassified
“…Christian schools: The exception, rather than the rule Although historians of education agree that no distinctively Christian educational system developed in antiquity, several New Testament scholars have suggested that one of the models for the Pauline ekklesia was the school (Conzelmann 1965;Judge 1960;Meeks 1983). However, as Wayne A. Meeks observes, the phrase &dquo;school of Paul&dquo; has often been used &dquo;quite loosely, referring merely to some continuity of thought and traditions that persisted for a time and could be distinguished from other trends in early Christianity&dquo; (1983: 82).…”
Section: Schools In Antiquitymentioning
confidence: 99%